2002
DOI: 10.1038/sj.onc.1205980
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin-induced activation of the EGF receptor

Abstract: Cisplatin (CDDP) is an efficient DNA-damaging antitumor agent employed for the treatment of various human cancers. CDDP activates nuclear as well as cytoplasmatic signaling pathways involved in regulation of the cell cycle, damage repair and programmed cell death. Here we report that CDDP also activates a membrane-integrated protein, the epidermal growth factor receptor (EGFR). We show that EGFR is activated in response to CDDP in various types of cells that overexpress the receptor, including transformed huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
101
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(118 citation statements)
references
References 43 publications
16
101
1
Order By: Relevance
“…Ultraviolet irradiation of cells can induce ERK activation, which serves as a survival signal: in this case, ERK activation occurs via SFK-dependent phosphorylation of EGF-R and subsequent downstream signaling (Kitagawa et al, 2002). Similarly, cisplatin-induced activation of EGF-R occurs via SFKs and results in protection (Benhar et al, 2002). These data suggest that DNA-damaging agents can generate survival signals that may be dependent on the regulation of RTKs by SFKs.…”
Section: Ubiquitinationmentioning
confidence: 84%
“…Ultraviolet irradiation of cells can induce ERK activation, which serves as a survival signal: in this case, ERK activation occurs via SFK-dependent phosphorylation of EGF-R and subsequent downstream signaling (Kitagawa et al, 2002). Similarly, cisplatin-induced activation of EGF-R occurs via SFKs and results in protection (Benhar et al, 2002). These data suggest that DNA-damaging agents can generate survival signals that may be dependent on the regulation of RTKs by SFKs.…”
Section: Ubiquitinationmentioning
confidence: 84%
“…One possibility is that gemcitabine-mediated EGFR phosphorylation might be due to activation of c-Src, as gemcitabine induced EGFR phosphorylation at tyrosine 845, which is a known c-Src kinase target (Sato et al, 1995). This pathway of EGFR activation has been implicated previously in response to cisplatin (Benhar et al, 2002). On the other hand, it has been shown that phosphorylation of Y1045, which is a cbl binding site, is necessary for ubiquitination of EGFR.…”
Section: Figurementioning
confidence: 98%
“…Such stimuli include several different reactive oxygen and nitrogen species, such as hydrogen peroxide (21) or peroxynitrite (28), as well as heavy metal ions (29) or anticancer agents such as cisplatin (30).…”
Section: Discussionmentioning
confidence: 99%